2003
DOI: 10.1002/clc.4960260412
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial inflow propagation rate derived by transesophageal color M‐mode echocardiography is a promising index of preload

Abstract: SummaryBackground: Pulmonary capillary wedge pressure (PCWP) is a useful index of preload and an important determinant of cardiac function.Hypothesis: We postulated that the rate of blood propagating into the left atrium (LAIF-PR) would be a useful measure of PCWP in critically ill patients.Methods: Fifty-two critically ill patients (36 men/16 women) receiving mechanical ventilation were studied by multiplane transesophageal echocardiography (TEE). Left atrial inflow propagation rate was measured in systole an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
1
4
1
Order By: Relevance
“…Mean LAIF-PV in our study was 24.2 cm/s, which is markedly lower than that previously reported in healthy volunteers (228 cm/s) and in critically ill patients (40 cm/s) [ 12 , 22 ]. A discrepancy likely explained by different clinical settings.…”
Section: Discussioncontrasting
confidence: 85%
See 4 more Smart Citations
“…Mean LAIF-PV in our study was 24.2 cm/s, which is markedly lower than that previously reported in healthy volunteers (228 cm/s) and in critically ill patients (40 cm/s) [ 12 , 22 ]. A discrepancy likely explained by different clinical settings.…”
Section: Discussioncontrasting
confidence: 85%
“…Stoddard et al found LAIF-PV feasible in 94% of a heterogeneous cohort of critically ill patients treated with mechanical ventilation [ 22 ]. Importantly, the LAIF-PV measurements in this study were obtained from transesophageal echocardiography (TEE).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations